2013
DOI: 10.1038/jcbfm.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-29b following Acute Ischemic Stroke Contributes to Neural Cell Death and Infarct Size

Abstract: Glutathione depletion and 12-lipoxygenase-dependent metabolism of arachidonic acid are known to be implicated in neurodegeneration associated with acute ischemic stroke. The objective of this study was to investigate the significance of miR-29 in neurodegeneration associated with acute ischemic stroke. Neural cell death caused by arachidonic acid insult of glutathionedeficient cells was preceded by a 12-lipoxygenase-dependent loss of miR-29b. Delivery of miR-29b mimic to blunt such loss was neuroprotective. mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 43 publications
(110 reference statements)
6
110
1
Order By: Relevance
“…Delivery of miR-29b mimic reduced 50% of strokeinduced brain lesion after 48 hours transient cerebral ischemia. 13 We found that miR-29b overexpression reduced brain infarct volume, alleviated brain edema, and attenuated the BBB damage. However, Shi et al 33 found that upregulated miR-29b promoted neuronal cell death after ischemic brain injury.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Delivery of miR-29b mimic reduced 50% of strokeinduced brain lesion after 48 hours transient cerebral ischemia. 13 We found that miR-29b overexpression reduced brain infarct volume, alleviated brain edema, and attenuated the BBB damage. However, Shi et al 33 found that upregulated miR-29b promoted neuronal cell death after ischemic brain injury.…”
Section: Discussionmentioning
confidence: 90%
“…32 The loss of miR-29b in the infarct region contributed to the injury of focally ischemic brain. 13 Another study reported that the miR-29b increased after cerebral ischemia. However, this study measured miR-29b in whole brain after stroke, which might mask changes in different focal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…http://dx.doi.org/10.1101/245928 doi: bioRxiv preprint first posted online Jan. 10, 2018; REST, activated by global ischemia. Over-expression of individual miR-29 family members has shown to improve stroke outcome in animal models by reducing infarct volume (Pandi et al, 2013, Wang et al, 2015, Khanna et al, 2013, and enhance post-stroke sensorimotor function (Khanna et al, 2013). The proposed mechanism of neuroprotection for each of these studies differ, and include the activation of DNA methyltransferase, DNMT3a, upon miR-29c loss (Pandi et al, 2013) and attenuating blood brain barrier disruption and subsequent vasogenic edema formation through relieving miR-29b repression of AQP4 (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One of the earlier reports suggests that downregulation of miR29b after acute ischemic stroke contributes to neural cell death and infarct size. 7 However, one report describes that upregulation of miR29b after ischemic brain injury promotes neuronal cell death by inhibiting Bcl2L2. 8 As these studies do not throw light on the role of miR29b in BBB disruption and reports about this microRNA are lacking, the significance of our study lies in drawing a clear picture on how miR29b can affect BBB.…”
Section: Introductionmentioning
confidence: 99%